Kimyasal Arıtma İşlemi Görmüş Evsel Atıksuların Membran Proseslerle Arıtmaya Uygunluğunun Araştırılması - Konuk, Melis (Fen Bilimleri Enstitüsü, 2014)
Endüstrinin gelişmesi ve hızlı nüfus artışı sebebiyle oluşan atıksular alıcı ortamların kirlenmesine neden olmaktadır. Bu nedenle atıksuların uzaklaştırılmadan önce arıtılması zorunluluğu doğmuştur. Yüksek askıda katı madde (AKM) ve organik madde içeren evsel atıksuların arıtılmasında genellikle ön çöktürme, aktif çamur sistemleri ve çamur stabilizasyonu içeren konvansiyonel biyolojik arıtma sistemleri kullanılmaktadır. Ancak bu sistemlerde oluşan aşırı biyolojik çamurun uzaklaştırılması işletme maliyetini büyük oranda arttırmaktadır. Bu sebeple evsel atıksu arıtımında aktif çamur sistemlerine alternatif olabilecek yeni sistemlerin geliştirilmesi zorunluluğu doğmuştur. Özellikle gelişmekte olan ülkelerdeki sıkılaşan çıkış suyu standartları ve düşük enerjili teknoloji arayışları kimyasal ilavesi ile atıksuların arıtılması konusunu ön plana çıkarmıştır. Bu çalışmada evsel atıksuların ileri kimyasal birincil arıtma (CEPT) ile arıtılabilirliği incelenmiştir. Kimyasal arıtmanın ilk amacı optimum koagülan tipi, optimum koagülan dozu ve optimum flokülan tipinin belirlenmesi olmuştur. Çalışma boyunca evsel atıksu özelliğine sahip Paşaköy İleri Biyolojik Atıksu Arıtma Tesisi’nden temin edilen kum tutucu çıkışı atıksuların karakteristiğini belirlemek amacıyla KOİ, süzülmüş KOİ, TKN, NH4-N, TP, PO4-P, AKM, UAKM ve pH analizleri yapılmıştır. Kimyasal ön arıtma çalışmalarında koagülan olarak ticari koagülanlardan Pac-s (Rapidfloc-1223), ULTRION(R) 71225, ULTRION 71230, NALCO 71260, NALCO 71975, NALCOLYTE 7135 ve FeCl3 kullanılmıştır. Flokülan cinsi olarak anyonik flokülanlardan WET-Treat® 7053 ve katyonik flokülanlardan WET-Treat® 7012 kullanılmıştır. Ayrıca kimyasal arıtılabilirlik flokülan kullanılmadan da incelenmiştir. Flokülan dozaj miktarı %0,1 olarak sabit tutulmuştur. Optimum dozlar KOİ giderimine ve çamur oluşumuna bağlı olarak belirlenmiştir. Sonuç olarak 250 mg/L FeCl3 ve anyonik polielektrolit WET-Treat® 7053 ve 0,5 ml Pac-s ve anyonik polielektrolit WET-Treat® 7053 dozları optimum doz olarak tespit edilmiştir. Arıtma proseslerinde dönüşüm mekanizmalarının anlaşılması açısından oldukça kullanışlı bir araç olarak uygulanan partikül boyut dağılımı analizi (PBD), biyolojik ve fizikokimyasal prosesler öncesinde atıksuların veya arıtılmış suların karakterizasyonu hakkında kapsamlı bilgi sağlamakta ve partiküler, kolloid ve çözünmüş boyuttaki kirleticilerin dağılımını göstermektedir. Bu çalışmada PBD koagülasyon-flokülasyon prosesinin verimini belirlemekle beraber deşarj parametrelerinin sağlanması amacıyla birincil kimyasal arıtma sonrasında uygulanabilecek ileri arıtma teknolojilerinden membran filtrasyonu kullanılacak ise hangi tip membran filtrasyonunun yeterli olabileceği hakkında bilgi vermektedir. Sonuç olarak kimyasal arıtma uygulanmış evsel atıksuların ardışık olarak filtrasyon-ultrasiltrasyon metodu ile partikül boyutlarının dağılımı belirlenmiş, genel olarak partiküllerin ham atıksularda %55-%58’inin partiküler formda, %23’ünün ise çözünür formda olduğu belirlenmiştir. Optimum doz olarak belirlenen 250 mg/L FeCl3 ve anyonik polielektrolit dozunda jar test üstsuyunun partiküler formu %20 iken, çözünür formu %35; optimum dozun altında kalan 100 mg/L FeCl3 ve anyonik polielektrolit dozunda jar test üstsuyunun ise partiküler formu %25, çözünür formu ise %39 olarak belirlenmiştir. Bir diğer optimum doz olan 0,5 ml Pac-s ve anyonik polielektrolit dozunda jar test üstsuyunun ise partiküler formu %11, çözünür formu %16 iken; optimum dozun altında kalan 0,1 ml Pac-s ve anyonik polielektrolit dozunda jar test üstsuyunun partiküler formu %38, çözünür formu ise %56 olarak belirlenmiştir. Ayrıca kimyasal arıtma sonrasında uygulanabilecek olan mikrofiltrasyon membranlarının deşarj standartlarını fazlasıyla karşılayacağı belirlenmiştir. Microsizer ile yapılan partikül boyut analizinde ise optimum doz olarak belirlenen 250 mg/L FeCl3 ve anyonik polielektrolit ve 0,5 ml Pac-s ve anyonik polielektrolit, optimum dozun altında kalan 100 mg/L FeCl3 ve anyonik polielektrolit ve 0,1 ml Pac-s ve anyonik polielektrolit dozlarının jar test üstsularının yanısıra ham atıksu numunesi de partikül boyut analizine tabii tutulmuş ve atıksulardaki partiküllerin hacimce %50’sini içeren boyutlar sırasıyla 151,552 μm, 211,073 μm, 108,164 μm, 69,305 μm ve 36,26 μm şeklinde bulunmuştur. Sonuç olarak 211,073 μm ile en büyük boyut olan 0,5 ml Pac-s ve anyonik polielektrolit dozunda en büyük flok oluşumunun gerçekleştiği ortaya konmuştur. Optimum ve optimum dozun altında belirlenen dozlar ile yapılan jar test sonucu kimyasal arıtılabilirlik çalışmalarında oluşan kimyasal çamurların susuzlaşabilme özelliğinin değerlendirilmesi amacıyla kapiler emme süreleri (KES) incelenmiş ve sonuçlar 250 mg/L FeCl3 ve anyonik polielektrolit dozu için 23,8 s, 100 mg/L FeCl3 ve anyonik polielektrolit dozu için 78,7 s, 0,5 ml Pac-s ve anyonik polielektrolit dozu için 50,35 s, 0,1 ml Pac-s ve anyonik polielektrolit dozu için 150,7 s olarak bulunmuştur. Bu durumda en kolay susuzlaşabilen koagülan dozu 250 mg/L FeCl3 iken, diğer dozlarında KES‘lerinin yeterince düşük olduğu tespit edilmiştir.

Wastewater caused by industrial development and rapid population growth has led to contamination of the receiving environment. Therefore, the removal of wastewater must be treated before it is discharged. Domestıc wastewater, which contains high suspended solids (TSS) and organic matter, is generally treated by conventional biological treatment systems which have pre-sedimentation, activated sludge and stabilization units. On the other hand, removal of excess biological sludge in these systems is greatly increasing operating cost. For this reason, investigation and development of the new systems which will be the alternative of the conventional activated sludge systems is necessary. Particularly strict effluent standards in developing countries and researching for low-energy technology is highlighted the chemical enhanced primary treatment. In this study, treatability of municipal wastewater was investigated with chemically enhanced primary treatment (CEPT). During the study, sewage feature wastewater obtained from Paşaköy Advanced Biological Wastewater Treatment Plant sand trap outlet was used and was received wastewater characteristics to determine the COD, filtered COD, TKN, NH4-N, TP, PO4-P, TSS, VSS and pH analyzes were conducted. The first object of this study was to determine the optimum type of coagulant , the optimum dose of coagulant and the optimum type of flocculant. Pac-s (Rapidfloc-1223), ULTRION(R) 71225, ULTRION 71230, NALCO 71260, NALCO 71975, NALCOLYTE 7135 and FeCl3 were used as commercial coagulant types. Also, WET-Treat® 7053 (anionic flocculant) and WET-Treat® 7012 (cationic flocculant) were used as coagulation aids. Chemical treatability was also investigated without using flocculant. During the study flocculant dosage amount 0.1% was maintained. Optimal doses are determined depending on COD removal and sludge formation. As a result, 250 mg/L FeCl3 with anyonic polielectrolyte WET-Treat® 7053 and 0.5 ml Pac-s with anyonic polielectrolyte WET-Treat® 7053 doses have been determined as optimum doses. The significance of size distribution of pollutants is long recognized for the interpretation of wastewater characteristics, assessment of appropriate treatment technologies and estimation of expected removal performances. The size range of settleable pollutants in wastewater is commonly defined as above 105nm, which practically defines the performance of plain settling. Similarly, filters with pore sizes of 450 and 1600 nm help identify the size of particles that can be removed by means of chemical settling. Particles in wastewaters have conveniently been grouped into operational size categories, namely dissolved (<1nm), colloidal (1–103 nm), supracolloidal (103–105 nm) and settleable (>105 nm). Recently, ultrafiltration, among other methods, is successfully used to identify and differentiate wastewater pollutants within much narrower ranges (Sophonsiri and Morgenroth, 2004; Dogruel et al., 2006). The experimental data on particle size associated with different wastewaters is significant for the evaluation of not only physical and biological processes, but also chemical treatment systems. Consequently, research efforts have been directed towards using particle size information for a better understanding of biological processes (Levine et al., 1991; Sophonsiri and Morgenroth, 2004). In the study proposes direct particle size measurement by sequential filtration and ultrafiltration as a convenient method for wastewater characterization for appropriate treatment technology. It also explores the correlation between particle size distribution (PSD), chemical oxygen demand (COD) and total organic carbon (TOK) fractionation, as an index for chemical treatability. In this study, raw wastewater was exhibited two significant COD fractions at the particle size intervals of >1600 nm (particulate range, 55%-58%) and <2 nm (soluble range; 23%). Chemically treated wastewater with 250 mg/L FeCl3 and anionic polyelectrolyte was exhibited two significant COD fractions at the particle size intervals of >1600 nm (particulate range, 20%) and <2 nm (soluble range; 35%). Chemically treated wastewater with 100 mg/L FeCl3 and anionic polyelectrolyte were exhibited two significant COD fractions at the particle size intervals of >1600 nm (particulate range, 25%) and <2 nm (soluble range; 39%). Chemically treated wastewater with 0.5 ml Pac-s and anionic polyelectrolyte were revealed two significant COD fractions at the particle size intervals of >1600 nm (particulate range, 11%) and <2 nm (soluble range; 16%). Chemically treated wastewater with 0.1 ml Pac-s and anionic polyelectrolyte was shown two significant COD fractions at the particle size intervals of >1600 nm (particulate range, 38%) and <2 nm (soluble range; 56%). PSD also helps us to determine the type of membrane which can be used to obtain the discharge standards for the municipal wastewaters. The four predominate membranes used in industry are Reverse Osmosis (RO), Ultrafiltration (UF), Microfiltration (MF) and Nanofiltration (NF). The pore size on microfiltration membranes ranges from 0.1-5 𝜇m, and has the largest pore size of the four main membrane types. Its opres are large enough to filter out such things as bacteria, blood cells, flour, talc and many other kinds of fine dust in solution. Because its pores are relatively large compared to other membranes, it can be operated under low pressures and therefore low energy. Ultrafiltration has a pore size range of 0.1 𝜇m to 0.01 𝜇m. UF membranes reject particles such as silica, viruses, endotoxins, proteins, plastics and smog/fumes such as ZnO. Due to the decrease in pore size, the osmotic pressure required is higher than that of MF. Nanofiltration has a pore size range of 0.001-0.01 𝜇m. NF membranes can filter particles up to and including some salts, synthetic dies and sugars, however it is unable to remove most aqueous salts and metallic ions,as such, NF is generally confined to specialist uses. Reverse osmosis has a pore size range of 0.0001-0.001 𝜇m. It is by far the finest seraration material available to industry. It is used on a large scale for the desalination and purification of water as it filters out everything but water molecules, with pore sizes approaching the radius of some atoms in many cases. This pore size means it is the only membrane that can reliably filter out salt and methalic ions from water. The small pore size of RO membranes means that significant amount of osmotic pressure is required to force filtration. According to pore size ranges and PSD datas, microfiltration membranes are enough to obtain the discharge standards. Particule size analyses were also conducted with microsizer. As a result of this analysis, 50% by volume with the maximum size of 211.073 μm that at a dose of 0.5 ml Pac-s and anionic polyelectrolytes was appeared as having a largest floc formation. The dewatering process of the sewage sludge is an important part of the wastewater treatment. Dewatering greatly reduces the volume of sludge requiring handling and disposal and is a necessary process for disposal options. Dewaterability was determined by measuring Capillary Section Time (CST) values. In this study, CSTs of chemical treatment sludges were examined. As a result, CST for 250 mg/L FeCl3 with anionic polyelectrolyte, 100 mg/L FeCl3 with anionic polyelectrolyte, 0.5 ml Pac-s with anionic polyelectrolyte and 0.1 ml Pac-s with anionic polyelectrolyte dose were identified as 23.8 sec, 78.7 sec, 50.35 sec, and 150.7 sec, respectively. These results were revealed that CST of 250 mg/L FeCl3 with anionic polyelectrolyte dose, which is the smallest, is more easily dewatered. Also capillary suction time values of other doses were found to be quite low.
Chemically Enhanced Primary Treatment Of Domestic Wastewater And Investigation Of Treatability With Membrane Processes
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: Evsel atıksu; Kimyasal arıtım; CEPT; Koagülasyon; Flokülasyon; Domestic wastewater; Chemical Treatment; CEPT; Coagulation; Floculation